Optimization of Teak Wood Raw Material Inventory Using The EOQ Method at UD Gemilang, Gunungsitoli City - Ronald Berkat Yustin Hulu; Martha Surya Dinata Mendrofa; Sophia Molinda Kakisina; Jeliswan Berkat Iman Jaya Gea (PT. Maju Malaqbi Makkarana, 2025)
This study highlights the problem of managing teak wood raw materials in the form of boards at UD Gemilang, Gunungsitoli City. The company often experiences shortages or excess inventory due to a conventional ordering system that is not based on optimal demand calculations. This inefficiency causes wasteful costs and disrupts the smooth production process. The main objective of this study is to analyze current inventory management and apply the EOQ (Economic Order Quantity) method to determine the optimal order quantity, as well as evaluate its impact on cost efficiency and production operations. The EOQ method is expected to be a systematic and rational solution for managing inventory more efficiently. This study uses a descriptive quantitative approach. Data were collected through direct interviews with business owners and documentation of raw material purchasing and usage reports for 2024. The analysis was conducted using the EOQ formula to calculate the optimal order quantity, ordering costs, storage costs, safety stock, reorder point, and total inventory cost (TIC). The analysis results show that the optimal order quantity for teak wood raw materials is 282 boards, with an ordering frequency of 6 times a year. This number is more efficient than the actual ordering system which is carried out monthly without a fixed calculation. The recommended safety stock is 22 boards, with a Reorder Point (ROP) of 36 boards. The implementation of the EOQ method successfully reduced total inventory costs from Rp6,768,000 to Rp3,496,800.